2022
DOI: 10.1158/1538-7445.am2022-41
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 41: Multi-focal genomic dissection of synchronous primary and metastatic tissue from de novo metastatic prostate cancer

Abstract: Background: 10% of newly diagnosed prostate cancer presents with metastases. Known as de novo metastatic castrate-sensitive prostate cancer (mCSPC), it is disproportionally responsible for >50% of prostate cancer deaths. Cancer genotyping can identify vulnerabilities exploitable by targeted therapies, and promises to help prognosticate. However, tissue from de novo mCSPC is scarce; neither prostatectomy nor metastatic biopsy is standard, and it is unknown if diagnostic biopsies are representative of syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Local consolidation refers to managing local disease in addition to systemic therapy. Recently, Warner et al [32] suggested that the prostate could potentially serve as a reservoir for distinct primary tumor clones, enabling multiple metastatic seeding events in patients with synchronous prostate cancer. The implication may provide a compelling biological rationale for local consolidated therapy in this setting.…”
Section: Local Consolidated Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Local consolidation refers to managing local disease in addition to systemic therapy. Recently, Warner et al [32] suggested that the prostate could potentially serve as a reservoir for distinct primary tumor clones, enabling multiple metastatic seeding events in patients with synchronous prostate cancer. The implication may provide a compelling biological rationale for local consolidated therapy in this setting.…”
Section: Local Consolidated Therapymentioning
confidence: 99%
“…Further risk stratification is needed in this setting, and advanced imaging in conjunction with genomics and liquid biomarkers may suggest who may benefit from MDT. Warner et al [32] recently postulated that among patients with SLV prostate cancer, particularly those with tumors lacking TP53 inactivation, may derive the greatest benefit from MDT. Recently, it was also demonstrated that PSMApositive extracellular vesicles may be used to select patients for Stereotactic Body Radiation Therapy (SBRT) with the potential of improving radiographic and PSA progression free survival without the need for systemic treatment [12 && ].…”
Section: Metastases Directed Therapymentioning
confidence: 99%
“…Thus, treatment of the primary location of cancer may improve clinical outcomes simply by tumor volume reduction [16]. Additionally, specifically regarding de-novo OMPC, as recently demonstrated by Warner et al [17], genomic assessment of the primary tumor post-radical prostatectomy (RP) can offer valuable insights for the implementation of genomics-guided patient management. In their study, Warner et al [17] observed a significant discordance in genotypes between certain areas of the primary tumor and synchronous metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, specifically regarding de-novo OMPC, as recently demonstrated by Warner et al [17], genomic assessment of the primary tumor post-radical prostatectomy (RP) can offer valuable insights for the implementation of genomics-guided patient management. In their study, Warner et al [17] observed a significant discordance in genotypes between certain areas of the primary tumor and synchronous metastases. Another concept with the widespread adoption of PET imaging is that when conventional imaging is normal even in high-risk disease, yet PET demonstrates OMPC, robust data do suggest a benefit of RP versus nonlocal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Low pathological tumor content and poor DNA yield were frequently responsible for unsuccessful sequencing, an issue that pervasively impacts prostate core needle biopsies obtained at initial diagnosis. Furthermore, marked genomic spatial heterogeneity within the prostate can undermine the ability of a single prostate biopsy specimen to correctly identify the dominant genotype responsible for metastatic disease development ( 8 , 9 ). In patients with metachronous metastatic disease, substantial time can separate initial diagnosis and subsequent development of clinical metastases ( 10 ).…”
Section: Introductionmentioning
confidence: 99%